Enantioselective Synthesis of Azamerone - Landry, Matthew L. (J Am Chem Soc, 2019)
A concise and selective synthesis of the dichlorinated meroterpenoid azamerone is described. The paucity of tactics for the synthesis of natural product-relevant chiral organochlorides motivated the development of unique strategies for accessing these motifs in enantioenriched forms. The route features a novel enantioselective chloroetherification reaction, a Pd-catalyzed cross-coupling between a quinone diazide and a boronic hemiester, and a late-stage tetrazine [4+2]-cycloaddition/oxidation cascade.